Criminal Law Policy in Handling Digital Asset-Based Money Laundering in Indonesia - Dipo Lukmanul Akbar (Journal of Law and Legal Reform, 2020)
The rapid development of information technology has given birth to a variety of services with a variety of digital information facilities, where the sophistication of information technology-based products is able to integrate all information media so as to make the world become borderless and cause significant social, cultural, economic and law enforcement changes take place quickly. Nevertheless, the conditions in Indonesia which are growing and developing towards an information technology-based industrial society, in some cases are still lagging behind to follow the development of information technology. The concepts and theories used to analyze are Criminal Law Policy, Law Number 8 of 2010 concerning Money Laundering. The paper emphasized that the development of information technology that is developing now, especially in the field of digital assets is able to become an opportunity for money laundering. The paper highlighted that in the case of committing the crime of money laundering is carried out using the digital currency-based information technology method and can be used for cross-country trade. So that the crime of money laundering based on digital assets is very easy to do and can have a worldwide network.